The impact of regional industries and universities on (high) technology entrepreneurship - Marcel Hülsbeck; Elena N. Kitzinger (University of Augsburg, Chair of Management and Organization, 2011)
Similar to the creation and distribution of new knowledge through industrial R&D and university research, entrepreneurial activity tends to vary across regions. Therefore the regionalized production of new knowledge is a prerequisite of entrepreneurial innovation. Based on endogenous growth theory, in particular the so-called Griliches-Jaffe-Model of regional knowledge production, we investigate industrial and university characteristics as determinants of technologically oriented entrepreneurship. Using hand-collected data from multiple sources, our results clearly show that high technology entrepreneurship is highly dependent on regional knowledge production by industry and university, while medium technology entrepreneurship does largely not dependent on these factors.
Keywords: 650; Unternehmensgründung; Hochtechnologiesektor; Räumliche Verteilung; Wissenstransfer; Industrielle Forschung; Hochschulforschung; Spillover-Effekt